QUALITY OF RAW MILK AND ITS FATTY ACID COMPOSITION. - IAKUBCHAK, О. М.; МІDYK, S. V.; DANCHUK, V. V.; DUDCHENKO, N. YA.; VYGOVSKA, L. M. (Ukrainian Journal of Veterinary Sciences, 2021)
The study of the influence of the season on the organoleptic and physicochemical parameters of milk is still relevant. In addition, the ratio of fatty acids in the milk of cows characterizes the level of their feeding and the study of these indicators is relevant given the prevalence of adulteration of milk and dairy products with vegetable oils. The aim was to study individual indicators of raw milk quality depending on the season and its fatty acid composition. The material for the study was prefabricated chilled raw milk obtained at different times of the year on the dairy farm of NULES of Ukraine "Agronomic Research Station". The research was conducted in the accredited Ukrainian Laboratory of Quality and Safety of AIC NULES of Ukraine. Organoleptic, physicochemical, sanitary and hygienic were determined by generally accepted standard methods. The fatty acid composition of milk was investigated by gas chromatography. Extraction of lipids from milk was performed by the method of Folch. Analysis of LCD methyl esters was performed on a Trace GC Ultra gas chromatograph (USA) with a flame ionization detector. Identification of fatty acids was performed using a standard sample Supelco 37 Component FAME Mix. Quantitative evaluation of the fatty acid spectrum of milk fat lipids was performed by the method of internal normalization with their determination in percent. The study was performed in 2 parallels. Statistical processing of experimental data was performed by conventional methods of variation statistics. The probability of the difference in indicators was assessed by Student's t-test. Differences between the compared indicators were considered significant at the significance level P < 0.05. Studies have shown that milk organoleptic and physicochemical parameters of raw milk vary depending on the season. In terms of microbiological indicators, the milk corresponded to the first grade, although in winter, according to other indicators, it could be attributed to the extra, or at worst, to the highest grade. In addition, in winter the content of saturated fatty acids in milk increases. The content of unsaturated fatty acids increases in summer and autumn due to the presence of green mass and corn silage in the diet of cows. The obtained results can be used as a basis for preparing a diet to obtain milk with optimal content and ratio of fatty acids, which can become competitive in the market of raw milk to produce milk and dairy products of improved chemical composition, dietary, functional products, baby food.